PENGEMBANGAN LKPD BERBASIS KEARIFAN LOKAL KECAMATAN LAWANG-MALANG PADA SISWA KELAS 5 SD - Rizky Arianty; Arina Restian; Innany Mukhlishina (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2021)
This development research was conducted to produce the educational produsts that aim to solve the educational problems. The background of this research was needed, namely the students of SD Negeri 1 Sidoluhur to LKPD learning products that suit their needs. The development of LKPD based on local wisdom was developed by paying attention to the sudents according to their place of recidence, namely Lawang-Malang Disctrict. The purpose of this research is to describe the wisdom-based development of LKPD in Lawang-Malang District for fifth grade students of SD Negeri 1 Sidoluhur. This research was guided by the ADDIE model which is carried out in 5 stages, namely: Analysis, Design, Development, Imlementation and Evaluation. The subjets in this research were the students of fifth grade SD Negeri 1 Sidoluhur, who may have 30 students. Data collection was carried out through observation, interviews, questionnaires and documentation. In addition, the data in this research are in the form of quantitative and qualitative data which are processed and described in a measured manner based on the product developed. The validation of the teaching materials got a percentage of 88% with a very good category. Validation of the thematic learning got a percentage of 88.6% with a very good category. While, the percentage obtained from the results of the student response questionnaire was 98%.